Building digital platform ecosystems: A synthetization of fundamental design topics from a literature review - Thomas Goertler; Marcel Papert; Isabel Fischer; Malou Schmidt (Digital Business)
The purpose of this paper is to contribute to the existing body of research on digital platforms by adopting an ecosystem perspective and considering an established framework. Through our work, we synthesize previous findings related to digital platforms and provide new insights into their ecosystem design. To achieve this, we conducted a comprehensive literature review to identify and synthesize relevant findings. Using this framework, we conducted a qualitative content analysis that allowed us to derive design recommendations and aggregate related design themes from the reviewed publications. The results of our study reveal a detailed framework that includes various design topics tailored to different stakeholders within the platform ecosystem. In practical terms, our findings provide valuable guidance to practitioners to help them make informed design and resource allocation decisions in the context of complex transformation projects. The identified themes synthesize the activities necessary to develop a platform's ecosystem and can be viewed as a basic design framework. This framework can serve as a playbook for practitioners seeking to navigate digital transformation processes toward platform-based models. Given the critical role of platform design in both academic and practical domains, this study aims to synthesize existing research on digital platforms and offer a framework that considers possible design topics from a business ecosystem perspective. This contribution is particularly important given the growing importance of platform ecosystems in today's digital economy.